Synovial C-reactive protein features high negative predictive value but is not useful as a single diagnostic parameter in suspected periprosthetic joint infection (PJI). Issue 6 (June 2019) - Plate, A.; Anagnostopoulos, A.; Glanzmann, J.; Stadler, L.; Weigelt, L.; Sutter, R.; Kästli, M.; Zinkernagel, A.S.; Zingg, P.O.; Achermann, Y.
Highlights: Synovial fluid C-reactive protein has a high negative predictive value of 98%. In periprosthetic joint infections it is significant elevated. There is no additional advantage to the established MSIS criteria. Abstract: Objectives: Synovial fluid C-reactive protein (syCRP) has been recently described as a new biomarker in preoperative diagnostics to identify periprosthetic joint infections (PJI). The aim of this study was to evaluate syCRP in a large cohort of patients with suspected PJI and to calculate the optimal cut-off to diagnose PJI. Methods: Between September 2015 and June 2017, we prospectively included patients with suspected PJI, in which syCRP was additionally measured along with routine preoperative diagnostic serum and synovial biomarkers. We analysed the sensitivity and specificity of syCRP using receiver operating characteristic curves. Results: We included 192 cases (hip n  = 80, knee n  = 91, shoulder n  = 21) with a final diagnosis of PJI in 26 cases (14.0%). Combined for all joints, the syCRP values were significantly higher in the PJI group than in the no PJI group (median: 13.8 vs. 0 mg/l; p  < 0.001). The optimal cut-off (Youden Index: 0.71) for the PJI diagnosis combined for all joints was at a syCRP value of 2.9 mg/l with a sensitivity of 88%, a specificity of 82%, and a negative predictive value of 98%. Conclusions: SyCRP features high negative predictive value but is not useful as a single diagnostic parameter in suspected periprosthetic joint infection (PJI).